Pengaruh Penggunaan Model Pembelajaran Kooperatif Tipe Student Teams Achievement Divisions Terhadap Prestasi Belajar Ekonomi Ditinjau Dari Motivasi Belajar Siswa Kelas XI IPS SMA Regina Pacis Surakarta Tahun Pelajaran 2012/2013 - Rosalia Widiastuti; Sigit Santosa; Djoko Santoso Th (Jurnal Pendidikan Insan Mandiri, 2014)
This experimental research aims to find out the different on the impacts of using cooperative learning type Student Teams Achievement Divisions and lecturing towards the social program students’ achievement on economics subject. The second aim is to find out the difference of social program students having high motivation and those having low motivation towards their achievement on economics subject. The last objective is to find out the interaction impacts between and the level of motivation towards the social program students’ achievement on economics subject.The experimental research employed Quasi experiment in which there were experimental group and controlled group. Both were formed randomly. It was conducted in SMA Regina Pacis Surakarta at semester 2 in the academic year of 2012/2013. Among all students of social program, who are the population of this experiment, 34 of whom were in eleventh graders of social 2 and functioned as the experimental group using Student Teams Achievement Divisions.  While the controlled group involved 34 eleventh graders of social 3 who used lecturing. This experiment used purposive cluster technique and random sampling. The data was analyzed using two ways ANAVA with its normality is tested using Liliefors significant correction from Kolmogorov Smirnov Test and its homogeneity is tested using F test.From the analysis, it is found out that firstly there was significant difference on the impacts of cooperative learning type Student Teams Achievement Divisions and lecturing towards students’ achievement on economics subject which was shown by the value of F=3.576 and the value of P=0.000 (P<0.05). The second finding was that there was significant difference of students having high motivation and those having low motivation which was shown by the value of F=73.468 with the value of P=0.0000 (P<0.05). The last finding was that there was significant impact between learning model and students’ motivation on students’ achievement on economics subject which was shown by the value of F=5.434 with P=0.023 and P=0.023 (P<0.05).